Brain activation changes during positive and neutral emotion regulation task following brief mindfulness: an fMRI study - Balakrishnan, Dhiviya Gopal (2022)
Introduction: Mindfulness is used to bring awareness and focus to a present state of mind. It also enhances positive emotion where people with a mindfulness state have control of their emotion and reduces the regulation of negative emotion. Objective: This study focuses to identify the associated brain activation of positive and neutral emotion regulation task following brief mindfulness exercises. Methodology: This study focuses on the healthy and young adult population. A neurotechnology tool is used which is functional magnetic resonance imaging (fMRI) to identify the brain activation of positive and neutral emotions. The positive and neutral emotion regulation task which was measured during the pre and post task consisted of positive word and neutral word stimuli which are extracted from Affective Norms for English Words (ANEW). Mindfulness state is assessed using the Mindful Attention Awareness Scale (MAAS) and the affect of the positive emotion regulation task is assessed using the Positive Affect and Negative Affect Scale – Expanded (PANAS-X). Results: Six participants were included in this study. The mindfulness group for positive emotion showed activation in the inferior frontal operculum, tri – inferior frontal, superior frontal and calcarine, while the neutral emotion showed activation in Rolandic operculum, postcentral gyri, calcarine and precentral gyri. The response time for both groups was insignificant (p > 0.05) but displayed a large size effect over the post-task. The positive effect for both groups was insignificant (p > Introduction: Mindfulness is used to bring awareness and focus to a present state of mind. It also enhances positive emotion where people with a mindfulness state have control of their emotion and reduces the regulation of negative emotion. Objective: This study focuses to identify the associated brain activation of positive and neutral emotion regulation task following brief mindfulness exercises. Methodology: This study focuses on the healthy and young adult population. A neurotechnology tool is used which is functional magnetic resonance imaging (fMRI) to identify the brain activation of positive and neutral emotions. The positive and neutral emotion regulation task which was measured during the pre and post task consisted of positive word and neutral word stimuli which are extracted from Affective Norms for English Words (ANEW). Mindfulness state is assessed using the Mindful Attention Awareness Scale (MAAS) and the affect of the positive emotion regulation task is assessed using the Positive Affect and Negative Affect Scale – Expanded (PANAS-X). Results: Six participants were included in this study. The mindfulness group for positive emotion showed activation in the inferior frontal operculum, tri – inferior frontal, superior frontal and calcarine, while the neutral emotion showed activation in Rolandic operculum, postcentral gyri, calcarine and precentral gyri. The response time for both groups was insignificant (p > 0.05) but displayed a large size effect over the post-task. The positive effect for both groups was insignificant (p > 0.05) but the audiobook group, showed a medium size effect while the mindfulness group showed a large size effect in the positive affect of PANAS – X. Conclusion: Visual, motor, and language had higher activation which would be defined by the presence of the audiobook and mindfulness audio and word stimuli while the mindfulness audio group showed a slight regulation of positive emotion. The small sample size showed the reduced efficiency of the results, but the large effect size indicated that differences in response time and positive effects are worth to be conducted in future studies. The study is suggested to be expanded to all age groups. In this preliminary study, a brief mindfulness exercise with 15 minutes time frame was able to identify the emotional effect on an individual.